K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 11 2016

\(\frac{x+1+3}{x+1}=\frac{x+1}{x+1}+\frac{3}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(3\right)=\left\{1;-1;3;-3\right\}\)

\(\Rightarrow x\in\left\{0;-2;2;-4\right\}\)

23 tháng 11 2016

Ta có :

\(x+1+3⋮x+1\)

=> \(x+1+3-\left(x+1\right)⋮x+1\)

=> \(3⋮x+1\)

=> \(x+1\inƯ_3\)

=> \(x+1\in\left\{1;3;-1;-3\right\}\)

=> \(x\in\left\{0;2;-2;-4\right\}\)

23 tháng 11 2016

\(\frac{x+5}{x+1}=\frac{x+4+1}{x+1}=\frac{x+1}{x+1}+\frac{4}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)

\(\Rightarrow x\in\left\{0;1;3;-2;-3;-5\right\}\)

23 tháng 11 2016

x+5\(⋮\)x+1

x+1+4\(⋮\)x+1

Vì x+1\(⋮\)x+1

Buộc 4\(⋮\)x+1=>x+1ϵƯ(4)={1;2;4}

Với x+1=1=>x=0

x+1=2=>x=1

x+1=4=>x=3

Vậy xϵ{0;1;3}

23 tháng 11 2016

Giải:

Ta có:

\(x+8⋮x+1\)

\(\Rightarrow\left(x+1\right)+7⋮x+1\)

\(\Rightarrow7⋮x+1\)

\(\Rightarrow x+1\in\left\{1;-1;7;-7\right\}\)

+) \(x+1=1\Rightarrow x=0\)

+) \(x+1=-1\Rightarrow x=-2\)

+) \(x+1=7\Rightarrow x=6\)

+) \(x+1=-7\Rightarrow x=-8\)

Vậy \(x\in\left\{0;-2;6;-8\right\}\)

23 tháng 11 2016

\(\frac{x+8}{x+1}=\frac{x+7+1}{x+1}=\frac{x+1}{x+1}+\frac{7}{x+1}\)

\(\Rightarrow x+1\in\text{Ư}\left(7\right)=\left\{1;7;-1;-7\right\}\)

\(\Rightarrow x\in\left\{0;6;-2;-8\right\}\)

23 tháng 11 2016

Ta có :

\(9⋮2x+1\)

=> \(2x+1\inƯ_9\)

=> \(2x+1\in\left\{1;3;9\right\}\)

=> \(2x\in\left\{0;2;8\right\}\)

=> \(x\in\left\{0;1;4\right\}\)

Vậy \(x\in\left\{0;1;4\right\}\)

23 tháng 11 2016

\(\frac{x+4}{x}=\frac{x}{x}+\frac{4}{x}\)

\(\Rightarrow x\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)

23 tháng 11 2016

Ta có :

\(x+4⋮x\)

=> \(x+4-x⋮x\)

=> \(4⋮x\)

=> \(x\inƯ_4\)

=> x\(\in\left\{1;2;4;-1;-2;-4\right\}\)

a: =-4xyz^2

b: =-9x^2y

c: =16x^2y^2

d: =1/6x^2y^3

e: =13/6x^3y^2

f: =7/12x^4y

30 tháng 5 2023

a) -xyz² - 3xz.yz

= -xyz² - 3xyz²

= -4xyz²

b) -8x²y - x.(xy)

= -8x²y - x²y

= -9x²y

c) 4xy².x - (-12x²y²)

= 4x²y² + 12x²y²

= 16x²y²

d) 1/2 x²y³ - 1/3 x²y.y²

= 1/2 x²y³ - 1/3 x²y³

= 1/6 x²y³

e) 3xy(x²y) - 5/6 x³y²

= 3x³y² - 5/6 x³y²

= 13/6 x³y²

f) 3/4 x⁴y - 1/6 xy.x³

= 3/4 x⁴y - 1/6 x⁴y

= 7/12 x⁴y

a: =-1/5x^5y^2

b: =-9/7xy^3

c: =7/12xy^2z

d: =2x^4

e: =3/4x^5y

f: =11x^2y^5+x^6

4 tháng 4 2023

\(1.x-\dfrac{2}{3}\times\left(x+9\right)=1\)

\(x-\dfrac{2}{3}\times x-6=1\)

\(x\times\left(1-\dfrac{2}{3}\right)=7\)

\(x\times\dfrac{1}{3}=7\)

\(x=21\)

\(2.x-\dfrac{11}{15}=\dfrac{3+x}{5}\)

\(\dfrac{15x}{15}-\dfrac{11}{15}=\dfrac{9+3x}{15}\)

\(15x-11=9+3x\)

\(12x=20\)

\(x=\dfrac{5}{3}\)

20 tháng 12 2021

1C

2A

11 tháng 7 2024

1C        2A